Han dynasty (206BC-AD220) stone carved tombs in central and eastern China - Li, C (2015)
This thesis studies Han Dynasty stone carved tombs in Central and Eastern China. These multi-chambered tombs were constructed from carved stone slabs, and were very popular among the Han people. However, such horizontal stone structures were entirely new, and were a result of outside stimuli rather than an independent development within China. The stone carved tombs were a result of imitating royal rock-cut tombs, while the rock-cut tombs were stimulated by foreign examples. Moreover, many details of stone carved tombs also had Western features. These exotic elements were incorporated to satisfy specific requirements of the Han people, and reflected the desire to assimilate exotica within Chinese traditions. Some details within stone carved tombs showed high level of stone working technologies with Western influences. But in general the level of stone construction of the Han period was relatively low. The methods of construction showed how unfamiliar the Western system was to the Han artisans. Han Dynasty stone carved tombs were hybrids of different techniques, including timber, brick and stone works. From these variations, Han people could choose certain types of tombs to satisfy their specific ritual and economic needs. Not only structures, but also pictorial decorations of stone carved tombs were innovations. The range of image motifs is quite limited. Similar motifs can be found in almost every tomb. Such similarities were partly due to the artisans, who worked in workshops and used repertoires for the carving of images. But these also suggest that the tombs were decorated for certain purposes with a given functional template. Together with different patterns of burial objects and their settings, such images formed a way through which the Han people gave meaning to the afterworld. After their heyday, stone carved tombs ceased being constructed in the Central Plains as the Han Empire collapsed. However, they set a model for later tombs. The idea of building horizontal stone chamber tombs spread to Han borderlands, and gradually went further east to the Korean Peninsula. The legacy and spread of the Chinese masonry tradition was closely related to the political circumstances of late Han and post-Han period. The spread of stone chamber tombs in Northeast Asia is presented as a part of a long history of interactions between different parts of Eurasia.